Evaluation Of Agility Of National Center for Gifted In Soccer Players Aged 14 – 16 Years - Abbas, Amar; Abdul Latif, Mohammed (Journal of Physical Education, 2017)
Soccer is considered one of the sports that require speed and agility during performance. The aim of this study to select physical tests for soccer players of the national center for gifted in soccer aged 14 – 16 years to evaluate the training program. The main subjects were (20) soccer players divided into three groups for four months each test is separated from the other test 35 day. The data was collected and treated using proper statistical operations. The results were displayed, analyzed then discussed to come up with the conclusions and recommendations. The researcher concluded that the training program developed agility and translational speed in players in the three test experiments